Metal particle-containing composition, bonding paste, and bonded body
By using metal particles with a particle size of 100nm to 500nm and compounds with multiple functional groups, combined with a high boiling point dispersion medium, to form a bonding paste, the problems of insufficient bonding strength and strength reduction after hot and cold cycles are solved, and efficient Bonding and printing adaptability.
Patent Information
- Application Number
- CN202280096169.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-20
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, the bonding strength of the metal member is insufficient and decreases with hot and cold cycles, resulting in insufficient fluidity of the bonding material and poor printing adaptability.
A composition containing metal particles (A) with an average particle diameter of 100 nm to 500 nm and a compound (B) with two or more functional groups is combined with a dispersion medium (C) with a boiling point of 200° C. or higher to form a bonding paste. The composition maintains the fluidity of the coating film through the high non-volatility and high viscosity of the compound (B), and forms a dense joint layer during the sintering process.
It achieves an increase in bonding strength and suppresses the decrease in bonding strength after hot and cold cycles, while maintaining the fluidity and printing adaptability of high-concentration metal particles, forming a stronger bonded body with fewer defects.
Smart Images

Figure BDA0005136778560000221 
Figure BDA0005136778560000231 
Figure BDA0005136778560000241
Abstract
Description
Technical Field
[0001] The present disclosure relates to a metal particle-containing composition, a bonding paste, and a bonded body. Background Art
[0002] In the past, solder has been used as a bonding material for bonding metal components to each other, metal components to semiconductor elements, metal components to light emitting diode (LED) elements, etc. In recent years, in the technical field of next-generation power electronics, devices such as SiC that can operate at high temperatures are required. As a bonding material for manufacturing such devices, from the perspective of high-temperature driving reliability, an alternative material to solder is required. For example, as shown in Patent Documents 1 to 3, a bonding material such as a bonding paste using sinterable metal particles is proposed.
[0003] Patent Document 1 discloses a bonding material comprising metal submicron particles having an average primary particle size of 0.5 μm to 3.0 μm, and metal nanoparticles having an average primary particle size of 1 nm to 200 nm and coated with an organic compound having a carbon number of 6 to 8. However, there are problems such as insufficient bonding strength of the bonded portion and decreased bonding strength with thermal cycling.
[0004] Patent document 2 discloses a bonding material comprising silver nanoparticles having an average primary particle size of 1 nm to 200 nm and coated with an organic substance having a carbon number of 8 or less, and a flux component having at least two carboxyl groups. In addition, patent document 3 discloses a bonding material comprising silver microparticles having an average primary particle size of 17 nm, 85 nm, and 0.6 μm, and a cross-linked inter-particle distance retaining agent for maintaining the spacing between the silver microparticles.
[0005] However, even these bonding materials have the same problem as the technology disclosed in Patent Document 1 that the strength of the bonded portion is insufficient and the bonding strength decreases with the cold and hot cycles. Furthermore, in order to achieve a dense and strong bond, in the case of making a bonding paste containing silver nanoparticles at a high concentration, there is also a disadvantage of significantly insufficient fluidity. As a result, there is the following problem: in the process of printing the bonding paste on the body to be bonded, white spots are generated in the printed part, or a non-coated part is formed.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-080147
[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-240406
[0010] Patent Document 3: Japanese Patent Application Publication No. 2018-109232 Summary of the invention
[0011] The properties required of a bonding paste using metal particles include, in addition to printability for a bonded body and sufficient bonding strength, minimal reduction in bonding strength after reliability tests such as thermal cycling.
[0012] Therefore, the problem to be solved by the present disclosure is to provide a composition containing metal particles and a bonding paste, which have high bonding strength at the bonded part and suppress the decrease of bonding strength accompanying the hot and cold cycle. In addition, a bonding paste is provided, which, in addition to the above characteristics, has excellent printing adaptability to the bonded body even if it contains metal particles at a high concentration. Furthermore, a bonded body that will not deteriorate due to hot and cold cycles is provided.
[0013] The inventors have repeatedly conducted research to solve the above problems, and as a result, the present disclosure is completed. A composition containing metal particles according to one embodiment of the present disclosure comprises: metal particles (A) having an average particle size of 100 nm to 500 nm; and a compound (B) having two or more functional groups (b) and a carbon number of 20 to 80, wherein the functional group (b) is any one selected from a hydroxyl group, a carboxyl group, and an amino group.
[0014] In the metal particle-containing composition according to one embodiment of the present disclosure, the number of the functional groups is 2 or 3.
[0015] In the metal particle-containing composition according to one embodiment of the present disclosure, the compound (B) has a branched and / or cyclic structure.
[0016] In the metal particle-containing composition according to one embodiment of the present disclosure, when the number of the functional groups is n, the compound (B) has an n-valent hydrocarbon group.
[0017] In the metal particle-containing composition according to one embodiment of the present disclosure, the n-valent hydrocarbon group has 30 to 60 carbon atoms.
[0018] In the metal particle-containing composition according to one embodiment of the present disclosure, the compound (B) includes one or more selected from the group consisting of dimer acid, trimer acid, dimer diol, trimer triol, dimer diamine, and trimer triamine.
[0019] The metal particle-containing composition according to one embodiment of the present disclosure contains 0.1 to 3 parts by mass of the compound (B) relative to 100 parts by mass of the metal particles (A).
[0020] The metal particle-containing composition according to one embodiment of the present disclosure contains 0.3 to 2.7 parts by mass of the compound (B) relative to 100 parts by mass of the metal particles (A).
[0021] In the metal particle-containing composition according to one embodiment of the present disclosure, the compound (B) includes a compound (Bx) having three carboxyl groups and having 20 to 80 carbon atoms.
[0022] In the metal particle-containing composition according to one embodiment of the present disclosure, the compound (Bx) is a trimer acid.
[0023] In the metal particle-containing composition according to one embodiment of the present disclosure, the compound (B) further includes a compound (By) having two carboxyl groups and having 20 to 80 carbon atoms.
[0024] In the metal particle-containing composition according to one embodiment of the present disclosure, the compound (By) is a dimer acid.
[0025] The metal particle-containing composition according to one embodiment of the present disclosure contains 0.05 to 2.7 parts by mass of the compound (Bx) relative to 100 parts by mass of the metal particles (A).
[0026] In the metal particle-containing composition according to one embodiment of the present disclosure, the metal particles (A) have an average particle diameter of 150 nm to 450 nm.
[0027] A joining paste according to one embodiment of the present disclosure contains a dispersion medium (C) and the metal particle-containing composition.
[0028] In the joining paste according to one embodiment of the present disclosure, the dispersion medium (C) includes a dispersion medium having a boiling point of 200° C. or higher.
[0029] In the joining paste according to one embodiment of the present disclosure, the dispersion medium (C) includes a dispersion medium having a boiling point of 250° C. or higher.
[0030] In the joining paste according to one embodiment of the present disclosure, the dispersion medium (C) includes one or more selected from the group consisting of glycol ether-based and glycol-based dispersion mediums.
[0031] In the joining paste according to one embodiment of the present disclosure, the ratio of the mass of the metal particles (A) to the mass of the joining paste is 80% by mass to 95% by mass.
[0032] In the joined body according to one embodiment of the present disclosure, the first joined portion and the second joined portion are joined by the joining paste.
[0033] According to the present disclosure, a composition containing metal particles and a bonding paste can be provided, wherein the bonding strength of the bonded part is high and the bonding strength does not decrease with the cold and hot cycles. In addition, a bonding paste having excellent printing adaptability in addition to these effects can be provided. Furthermore, a bonded body that does not deteriorate due to the cold and hot cycles can be provided. DETAILED DESCRIPTION
[0034] In this specification, “metal particles (A) having an average particle size of 100 nm to 500 nm” may be abbreviated as “metal particles (A)”, and “compound (B) having 20 to 80 carbon atoms and having a plurality of identical functional groups in the molecule” may be abbreviated as “compound (B)”.
[0035] The metal particle-containing composition disclosed herein contains metal particles (A) and a compound (B). In addition, the bonding paste contains the metal particles (A) and the compound (B) and also contains a dispersion medium (C). The metal particle-containing composition can be formed by volatilizing a part or all of the dispersion medium (C) from the bonding paste in the bonding process.
[0036] Regarding the composition containing metal particles disclosed herein, by combining metal particles (A) and compound (B), the high non-volatility and high viscosity of compound (B) can make the coating film fluid even in the state of coating. Thus, in the sintering stage of metal particles (A) having a predetermined particle size, the wettability to the substrate is improved and the adhesion is improved. Therefore, the generation of voids in the coating film can be suppressed to form a dense coating film, and excellent bonding strength or bonding strength after hot and cold cycles can be exerted.
[0037] <Metal particles (A)>
[0038] As the metal in the metal particle (A), for example, gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, platinum and alloys thereof can be listed. In addition, microparticles in which the core is coated with a substance different from the core substance can be listed, specifically, for example, a silver-coated copper powder with a copper core and a surface coated with silver, etc. can be listed. In addition, powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, ruthenium oxide, tin-doped indium oxide (Indium Tin Oxide, ITO), aluminum-doped zinc oxide (Aluminum Zinc Oxide, AZO), and gallium-doped zinc oxide (Gallium Zinc Oxide, GZO), as well as powders coated with these metal oxides, etc. can also be listed. The type of metal used can be one, or two or more can be used in combination.
[0039] In terms of obtaining a bonded body having particularly excellent strength, the metal particles (A) are preferably selected from copper or silver. Furthermore, in terms of being able to cope with a wide range of calcination temperatures and various calcination environments such as atmospheric pressure, nitrogen environment, vacuum or reduction environment, the metal particles (A) are more preferably silver.
[0040] The metal particles (A) have a function of melting or bonding each other (hereinafter also referred to as sintering) in the temperature range of 200°C to 350°C when the metal particle-containing composition or bonding paste is heated and sintered by being within a specific average particle size range, thereby being able to be transformed into a bulk metal. As a result, the bonding of the bonded bodies is completed. Hereinafter, the portion formed by the sintering of the metal particles (A) between the bonded bodies is referred to as a bonding layer.
[0041] In the present disclosure, it is important to use metal particles (A) having a specific average particle size. The so-called "average particle size" in this specification refers to the 50% cumulative particle size distribution particle size (d50) based on volume obtained by the measurement method described in the examples. The d50 of the metal particles (A) is 100nm to 500nm, preferably 150nm or more, more preferably 180nm or more, and more preferably 200nm or more. In addition, the d50 of the metal particles (A) is preferably 450nm or less, more preferably 350nm or less, and more preferably 300nm or less.
[0042] The metal particles (A) are preferably coated with an organic component (a). If coated with an organic component (a), it is expected that the storage stability of the composition containing the metal particles or the bonding paste will be improved. Examples of the organic component (a) include fatty acids, aliphatic amines, aliphatic alcohols, etc., preferably saturated or unsaturated fatty acids, more preferably saturated or unsaturated fatty acids with a carbon number of 3 to 18, and further preferably saturated or unsaturated fatty acids with a carbon number of 6 to 18. The organic component (a) may contain one or more than two.
[0043] The metal particles (A) can be used alone or in combination. In addition, metal particles other than the metal particles (A) can also be used in combination as needed. When metal particles other than the metal particles (A) are used in combination, metal particles having a particle size exceeding 500 nm in average particle size can be combined, and metal particles having a particle size exceeding 1000 nm in average particle size can also be combined.
[0044] <Compound (B)>
[0045] Secondly, the compound (B) is described. Usually, the metal particles are powders, so when the compound (B) is not included, as the dispersion medium described later evaporates from the bonding paste, it is difficult to form an interface with the bonded portion. However, by including the compound (B) disclosed herein, even after a portion or all of the dispersion medium (C) evaporates, a liquid composition containing metal particles can exist, so a good bonding interface that is integrated with the bonded portion can be formed.
[0046] The compound (B) has a structure having two or more functional groups selected from hydroxyl, carboxyl or amino groups (hereinafter, the functional groups are referred to as "functional groups (b)") in the molecule and having 20 to 80 carbon atoms.
[0047] The carbon number of compound (B) indicates a value including carbon atoms in functional group (b). Therefore, when functional group (b) in compound (B) is a carboxyl group, the carbon number including carbon atoms in the carboxyl group is regarded as the carbon number of compound (B).
[0048] In compound (B), the skeleton (partial structure) after removing the functional group (b) is an organic residue, but preferably a hydrocarbon group or a group formed by bonding a plurality of hydrocarbon groups using a linking group containing a hetero atom. Examples of such a linking group containing a hetero atom include: -O-group (ether group), -C(=O)-group (carbonyl group), -C(=O)-O-group (ester group or oxycarbonyl group), -C(=O)-NH-group (amide group or iminocarbonyl group). Compound (B) preferably does not have a functional group other than the functional group (b).
[0049] The properties of the compound (B) are not particularly limited, but it is preferably liquid in the temperature range of 200° C. to 350° C., which is the temperature range in which the metal particle-containing composition of the present disclosure is calcined. The compound (B) may be solid or liquid at room temperature (25° C.), but it is more preferably liquid at room temperature from the viewpoint of being uniformly dispersed in the metal particle-containing composition and effectively acting.
[0050] When compound (B) has the property of being liquid in the temperature region, it can be expected that the wettability at the joint interface of the joined portion is improved, and the contact area is increased. As a result, a joint body with a firm joint interface can be manufactured. In addition, it is considered that: even if a gap is formed in the joint layer during sintering, due to the improvement of the fluidity of the composition containing metal particles, the liquid compound (B) flows into the defective parts such as the gap, and a joint layer and a joint body with few defects can be obtained.
[0051] The number of functional groups (b) in the compound (B) is preferably two or three.
[0052] Compound (B) may have a linear structure or a branched and / or cyclic structure, preferably a branched and / or cyclic structure. In terms of low crystallinity and the ease of forming a liquid with good fluidity, a branched and / or cyclic structure is preferred.
[0053] When the number of functional groups (b) in compound (B) is n, compound (B) preferably has an n-valent hydrocarbon group. In compound (B), the skeleton after removing the functional groups (b) preferably contains only n-valent hydrocarbon groups in terms of obtaining a strong bond.
[0054] For the above reasons, the compound (B) preferably does not evaporate immediately at the start of sintering. However, it is not necessary for it to remain in the formed bonding layer at the end of sintering. When the number of carbon atoms in the n-valent hydrocarbon group is 30 to 60, the amount of the compound (B) remaining in the bonding layer after sintering can be further reduced, and a denser bonding layer can be easily obtained, so it is preferred. As a result, the initial bonding strength is excellent, and it can be further expected to suppress the decrease in bonding strength accompanying the hot and cold cycle.
[0055] Examples of the compound (B) having a linear structure include, but are not limited to, eicosanedioic acid, heneicosanedioic acid, docosanedioic acid, tetracosanedioic acid, triacontanedioic acid, dotriaconedioic acid, tetracontanedioic acid, pentacontanedioic acid, hexacontanedioic acid, and batalool.
[0056] Examples of the compound (B) having a branched and / or cyclic structure include, but are not limited to, dimer acid, trimer acid, tetramer acid, dimer diol, trimer triol, tetramer tetraol, dimer diamine, trimer triamine, tetramer tetraamine, and phytantriol.
[0057] Among them, as compound (B), for the reasons described above, a compound selected from the group consisting of dimer acid, trimer acid, dimer diol, trimer triol, dimer diamine, and trimer triamine is more preferred.
[0058] Dimer acid, trimer acid and tetramer acid can be manufactured by the polymerization reaction of unsaturated fatty acids. For example, it can be manufactured by the Diels-Alder reaction or free radical reaction of oleic acid (carbon number 18) and linolenic acid (carbon number 18). The carbon number of dimer acid is preferably 36 or 44, the carbon number of trimer acid is preferably 54, and the carbon number of tetramer acid is preferably 72. In addition, by appropriately changing the carbon number of the unsaturated fatty acids as raw materials, it is possible to manufacture compounds (B) with carbon numbers other than those described. In addition, in this manual, dimers, trimers and tetramers of unsaturated fatty acids with carbon numbers more than 12 are respectively referred to as dimer acid, trimer acid and tetramer acid.
[0059] The dimer diol has a structure in which the carboxyl group of the dimer acid is reduced to a hydroxyl group, the trimer triol has a structure in which the carboxyl group of the trimer acid is reduced to a hydroxyl group, and the tetramer tetraol has a structure in which the carboxyl group of the tetramer acid is reduced to a hydroxyl group. The carbon number of the dimer diol is preferably 36, the carbon number of the trimer triol is preferably 54, and the carbon number of the tetramer tetraol is preferably 72.
[0060] The dimer diamine has a structure in which the carboxyl group of the dimer acid is converted into an amino group by functionalization, the trimer triamine has a structure in which the carboxyl group of the trimer acid is converted into an amino group by functionalization, and the tetramer tetraamine has a structure in which the carboxyl group of the tetramer acid is converted into an amino group by functionalization. The number of carbon atoms in the dimer diamine is preferably 36, the number of carbon atoms in the trimer triamine is preferably 54, and the number of carbon atoms in the tetramer tetraamine is preferably 72.
[0061] The compound (B) may be a mixture of compounds having different degrees of polymerization depending on the production method, and may be used as a mixture of different polymers, or a specific single compound may be used.
[0062] In the metal particle-containing composition of the present disclosure, the compound (B) preferably contains 0.1 to 3 parts by mass, and more preferably contains 0.3 to 2.7 parts by mass, relative to 100 parts by mass of the metal particles (A). Within the above range, a bonded body having particularly excellent initial bonding strength and suppressing the decrease in bonding strength accompanying thermal cycling can be obtained.
[0063] [Compound (Bx)]
[0064] The composition containing metal particles disclosed in the present invention preferably contains a compound (Bx) having three carboxyl groups and a carbon number of 20 to 80 as compound (B). Compound (Bx) may be a straight chain structure or may have a branched and / or cyclic structure, preferably a branched and / or cyclic structure. In terms of low crystallinity and easy liquid formation with good fluidity, it is preferably a case of having a branched and / or cyclic structure. Compound (Bx) preferably has a trivalent hydrocarbon group. In compound (Bx), in terms of obtaining a strong joint, the skeleton after removing the carboxyl group is more preferably composed of only trivalent hydrocarbon groups. As a specific example of a compound (Bx) having a branched and / or cyclic structure, trimer acid can be cited, which can be preferably used.
[0065] The composition containing metal particles disclosed herein preferably contains 0.05 to 2.7 parts by mass of compound (Bx) relative to 100 parts by mass of metal particles (A). By using the amount in the above range, excellent bonding strength and thermal cycling characteristics can be achieved even under more stringent conditions such as when using a substrate to be bonded that has not been plated. The content of compound (Bx) is preferably 0.15 to 1.7 parts by mass. If it is within the above range, a bonded body with excellent initial bonding strength and thermal cycling properties can be obtained.
[0066] [Compound (By)]
[0067] The metal particle-containing composition disclosed in the present invention preferably further comprises a compound (By) having two carboxyl groups and a carbon number of 20 to 80 as compound (B). The volatilization or decomposition temperature of the compound (Bx) is different from that of the compound (By) having a different number of carboxyl groups, and the volatilization or decomposition temperature of the compound (By) is lower than that of the compound (Bx). Therefore, if these are used in combination, volatilization or decomposition together at a specific temperature can be suppressed in the sintering process of silver. Therefore, the coating film can be sintered in a state of maintaining high fluidity for a longer period of time. As a result, the adhesion with the joined portion is further improved, and a joint with fewer defects and a firmer joint can be obtained.
[0068] Compound (By) may be a linear structure, or may have a branch and / or cyclic structure, preferably a branch and / or cyclic structure. In terms of low crystallinity and being easily liquid with good fluidity, preferably a branch and / or cyclic structure. Compound (By) preferably has a divalent hydrocarbon group. In compound (By), in terms of obtaining a strong bonded body, the skeleton after removing the carboxyl group is more preferably only composed of divalent hydrocarbon groups.
[0069] Examples of the compound (By) having a linear structure include, but are not limited to, eicosanedioic acid, heneicosanedioic acid, docosanedioic acid, tetracosanedioic acid, triacontanedioic acid, dotriaconedioic acid, tetracontanedioic acid, pentacontanedioic acid, and hexacontanedioic acid. Examples of the compound (By) having a branched and / or cyclic structure include, for example, dimer acid, which can be preferably used.
[0070] In the metal particle-containing composition of the present disclosure, it is preferred that the total amount of the compound (Bx) and the compound (By) is 0.1 to 3.0 parts by mass, and more preferably 0.3 to 2.7 parts by mass, relative to 100 parts by mass of the metal particles (A). When the total amount of the compound (Bx) and the compound (By) is within the above range, a bonded body having particularly excellent initial bonding strength and in which a decrease in bonding strength accompanying thermal cycling is suppressed can be obtained.
[0071] <Dispersion medium (C)>
[0072] The bonding paste disclosed herein contains a dispersion medium (C) (excluding the compound (B)). The dispersion medium (C) has the function of dispersing the metal particles (A) and the compound (B). In addition, the dispersion medium (C) has the function of imparting fluidity to the coating film during the sintering process of silver. The carbon number of the dispersion medium (C) is preferably less than 20.
[0073] The dispersion medium (C) may be any medium capable of uniformly dispersing the metal particles (A) and the compound (B). Specific examples thereof include terpineol, dihydroterpineol, dihydroterpineol acetate, Terusolve MTPH (manufactured by Japan Terpene Co., Ltd.), Texanol (2,2,4-trimethylpentane-1,3-diol monoisobutyrate), carbitol, carbitol acetate, butyl carbitol, isophorone, γ-butyrolactone, dipropylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol methyl n-propyl ether, 3-methoxy-3-methylbutyl acetate, ethylene glycol, propylene glycol diacetate, dipropylene glycol methyl ether acetate, 1,3-butylene glycol (1,3-butylene glycol). The invention also includes, but is not limited to, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, polyethylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, and isoalkane solvents contained in hydrocarbon solvents.
[0074] The dispersion medium (C) preferably contains a dispersion medium having a boiling point of 200°C or more. If a dispersion medium having a boiling point of 200°C or more is contained, the dispersion medium in the coating film dries and decreases relatively slowly during the sintering process of silver, so the coating film can be sintered while maintaining high fluidity. As a result, it is possible to improve the adhesion with the joined portion, or obtain a joint with fewer defects and a firm body. The proportion of the dispersion medium having a boiling point of 200°C or more in the mass of the dispersion medium (C) is preferably 70% by mass or more.
[0075] The boiling point of the dispersion medium having a boiling point of 200°C or more is preferably 240°C or more, more preferably 250°C or more. If it is 250°C or more, the coating can be sintered while maintaining high fluidity for a longer period of time. Therefore, a joint with fewer defects and a strong structure is formed, and the thermal cycle performance is excellent, so it is preferred. In addition, from the viewpoint of suppressing the residue of the dispersion medium, the boiling point is preferably 350°C or less. In the case of containing a plurality of dispersion media having a boiling point of 200°C or more, the boiling point of the dispersion medium having a boiling point of 200°C or more can be calculated based on their respective boiling points and their mass ratios.
[0076] Examples of the dispersion medium having a boiling point of 200° C. or higher include terpineol, dihydroterpineol, dihydroterpineol acetate, Terusolve MTPH (manufactured by Japan Terpene Co., Ltd.), Texanol (2,2,4-trimethylpentane-1,3-diol monoisobutyrate), isophorone, γ-butyrolactone, dipropylene, 1,3-butanediol, 1,4-butanediol, 2-ethyl-1,3-hexanediol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, polyethylene glycol monobutyl ether, and hydrocarbon solvents having a boiling point of 200° C. or higher, but are not limited thereto. These dispersion media having a boiling point of 200° C. or higher may be used alone or in combination of two or more.
[0077] Among the dispersion media having a boiling point of 200°C or higher, preferably used are diols such as 1,3-butanediol, 1,4-butanediol, and 2-ethyl-1,3-hexanediol; and diol ethers such as diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, and polyethylene glycol monobutyl ether. More preferably, diol ethers are used. As dispersion media of diol ethers having a boiling point of 250°C or higher, particularly preferably used are diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, and polyethylene glycol monobutyl ether.
[0078] When sintering the bonding paste, when the boiling point of the dispersion medium (C) is lower than that of the compound (B), the amount of the dispersion medium (C) coexisting with the metal particle-containing composition during sintering can be reduced, and the content of the metal particles (A) can be increased, which is preferred.
[0079] <Manufacturing of bonding paste>
[0080] The bonding paste disclosed herein is used by combining metal particles (A) and compound (B), and even when the metal particles (A) are contained at a high concentration, that is, even when the content ratio of the dispersion medium (C) is low, it also exhibits excellent fluidity, and thus has excellent printing adaptability to the body to be bonded. As a result, a bonded body with fewer defects and stronger can be obtained.
[0081] In the bonding paste, the mass of the metal particles (A) is preferably 80% to 95% by mass, more preferably 85% to 94% by mass, in the sum of the masses of the metal particles (A), the compound (B) and the dispersion medium (C). In addition, the mass of the metal particles (A) is preferably 80% to 95% by mass, more preferably 85% to 94% by mass. By including the metal particles (A) in the above range, the bonding paste can exhibit good printing adaptability, and the residual dispersion medium (C) in the bonded body is suppressed, and the generation of voids caused by the dispersion medium (C) is suppressed, and good bonding strength is exhibited.
[0082] The joining paste of the present disclosure may contain additives, and may contain, for example, a sintering accelerator, a binder resin, or a resin-type dispersant.
[0083] Examples of an apparatus for preparing a bonding paste from the metal particles (A), the compound (B) and the dispersion medium (C) include a disperser, a three-roll mill, a bead mill, an ultrasonic disperser, and a rotation-revolution type agitator.
[0084] <Joint body>
[0085] The first joined part and the second joined part can be joined by the joining paste disclosed in the present invention to obtain a joined body. As a method for applying the joining paste to the joined body, there is no particular limitation as long as it is a method that can be evenly applied to the component, and examples thereof include: various printing methods such as screen printing, flexographic printing, lithographic printing, gravure printing, metal mask printing, gravure lithographic printing, and the like; and a spraying method using a dispenser, etc. The joining paste disclosed in the present invention has excellent fluidity even if it contains metal particles at a high concentration, and therefore it is particularly preferably used in combination with metal mask printing.
[0086] When placing the second bonded portion on the first bonded portion coated with the bonding paste of the present disclosure, the second bonded portion may be placed while applying pressure. The pressure is appropriately set according to the viscosity of the bonding paste or the dry state of the paste, preferably 0.1 MPa to 40 MPa, more preferably 0.3 MPa to 30 MPa.
[0087] The conditions for sintering the laminated body in which the first bonded part is loaded with the second bonded part can be appropriately changed, for example, conditions such as atmospheric pressure, nitrogen environment, vacuum, or reduction environment and 200°C to 350°C can be listed. As calcining devices, there can be listed: hot air oven, calcining furnace, electric furnace, infrared oven, reflow oven, microwave oven, heating plate, light calcining device, etc. These devices can be used alone or in multiples as appropriate. In addition, pressure can also be applied while sintering. Regarding pressure, it is appropriately set according to the viscosity of the bonding paste or the dry state of the paste, preferably 0.1MPa to 40MPa, and more preferably 0.3MPa to 30MPa.
[0088] Before the calcination step, a pre-drying step may be appropriately added to remove organic components in the bonding coating film. For example, the calcination step may be performed at a temperature of 60° C. to 220° C. using the same apparatus as the calcination apparatus.
[0089] As a preferred method for joining two joined parts, the following method can be cited: after applying the joining paste disclosed in the present invention to the first joined part, the second joined part is placed, and the temperature is raised to about 300°C at a heating rate of about 2°C / min to 30°C / min to perform sintering. Preferably, after the heating is completed, the temperature is maintained at a higher temperature than the temperature at the end of the heating for about 10 minutes to 2 hours.
[0090] The type of the joined part is not particularly limited. For example, in addition to metal materials, semiconductor materials, plastic materials, and ceramic materials, electronic components can also be listed. Examples of metals include copper, gold, and aluminum. Examples of semiconductor materials include silicon, germanium, gallium arsenide, gallium phosphide, cadmium sulfide, silicon nitride, graphite, yttrium oxide, magnesium oxide, silicon carbide, and gallium nitride. Examples of plastic materials include polyimide, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, and polyethylene naphthalate. Examples of ceramic materials include glass and silicon. Examples of electronic components include semiconductor components, LED components, and power device components.
[0091] The first joined portion and the second joined portion may be not only the same type of components but also different types of components. Regarding the joined portion, in order to increase the joining strength of the joined portion, the surface of the joined portion may be subjected to corona treatment, plating treatment, etc.
[0092] The thickness of the bonding layer formed when bonding parts using the metal particle-containing composition or bonding paste of the present disclosure is not limited, but is preferably 3 μm to 500 μm, more preferably 10 μm to 200 μm, and even more preferably 20 μm to 100 μm.
[0093] Example
[0094] Hereinafter, the present disclosure will be described in detail using examples and comparative examples, but the technical scope of the present disclosure is not limited thereto. In addition, in the examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively. Unless otherwise specified, the numerical values in the table represent "parts".
[0095] <Manufacturing of Metal Particles>
[0096] (Production Example 1) Metal Particle A1
[0097] Under nitrogen atmosphere, 200 parts of toluene and 22.3 parts of silver hexanoate were mixed while stirring at 25°C to prepare a 0.5M solution, and then 1.6 parts of diethylaminoethanol and 0.28 parts of oleic acid as dispersants were added and dissolved. Then, 73.1 parts of succinic acid dihydrazide (hereinafter referred to as SUDH) aqueous solution with a concentration of 20% as a reducing agent was added dropwise, and the color of the liquid changed from light yellow to dark brown. In order to further promote the reaction, the temperature was raised to 40°C and the reaction was carried out. After standing and separating, the aqueous phase was taken out to remove excess reducing agent or impurities, and distilled water was added to the toluene layer several times. After repeated washing and separation, toluene was added, and after centrifugation, the supernatant was removed, and the above process was repeated twice. The precipitate was dried to obtain metal particles A1 in which silver particles were coated with hexanoic acid and oleic acid. The particle size of metal particles A1 was obtained by the method described below, and the result was d50 of 210nm.
[0098] (Production Example 2) Metal Particles A2
[0099] Metal particles A2 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 1.8 parts and the amount of oleic acid was changed to 0.31 parts. d50 was 185 nm.
[0100] (Production Example 3) Metal Particles A3
[0101] Metal particles A3 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 1.2 parts and the amount of oleic acid was changed to 0.18 parts. d50 was 290 nm.
[0102] (Production Example 4) Metal Particle A4
[0103] Metal particles A4 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 1.0 part and the amount of oleic acid was changed to 0.14 part. d50 was 390 nm.
[0104] (Production Example 5) Metal Particle A5
[0105] Metal particles A5 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 0.6 parts and the amount of oleic acid was changed to 0.070 parts. d50 was 1100 nm.
[0106] (Production Example 6) Metal Particle A6
[0107] Metal particles A6 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 2.3 parts and the amount of oleic acid was changed to 2.8 parts. d50 was 20 nm.
[0108] (Production Example 7) Metal Particles A7
[0109] Metal particles A7 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 2.1 parts and the amount of oleic acid was changed to 0.71 parts. The d50 was 85 nm.
[0110] (Production Example 8) Metal Particles A8
[0111] Metal particles A8 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 2.4 parts and the amount of oleic acid was changed to 0.42 parts. d50 was 120 nm.
[0112] (Production Example 9) Metal Particles A9
[0113] Metal particles A9 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 2.0 parts and the amount of oleic acid was changed to 0.34 parts. d50 was 155 nm.
[0114] (Production Example 10) Metal Particle A10
[0115] Metal particles A10 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 1.4 parts and the amount of oleic acid was changed to 0.09 parts. d50 was 600 nm.
[0116] (Production Example 11) Metal Particle A11
[0117] Metal particles A11 were obtained in the same manner as in Production Example 1 except that the amount of diethylaminoethanol was changed to 2.2 parts and the amount of oleic acid was changed to 0.38 parts. d50 was 140 nm.
[0118] [Measurement of particle size]
[0119] Isopropyl alcohol was added to each metal particle (A), and dispersed using an ultrasonic disperser to obtain a dispersion of 0.5 mass %. For the obtained dispersion, the particle size of the metal particles in the dispersion was measured using Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) to determine the average particle size (d50). Among the metal particles manufactured by the method, metal particles A1-metal particles A4, metal particles A8-metal particles A9 and metal particles A11 are equivalent to the metal particles (A) of the present disclosure, and metal particles A5-metal particles A7 and metal particles A10 are equivalent to metal particles that are not metal particles (A).
[0120] <Production of Compound (B)>
[0121] (Production Example 12) Trimer triol (Compound B4)
[0122] With reference to the method described in Japanese Patent Laid-Open No. 10-67835, trimer triol was synthesized as follows. Under nitrogen atmosphere, 1000g of an unsaturated fatty acid ester mixture containing 75% methyl oleate, 15% methyl linoleate and 9% methyl stearate was reacted with 70g of activated clay in an autoclave at 230°C for 5 hours. The catalyst was filtered and separated from the reaction solution, and vacuum distillation was performed to obtain 115g of trimer acid trimethyl ester. In a flask including a dropping funnel, a cooling tube, a thermometer and a stirrer, 6.4g of lithium aluminum hydride and 240ml of diethyl ether were carefully mixed under nitrogen atmosphere to prepare a dispersion of lithium aluminum hydride. Under nitrogen atmosphere, while stirring the dispersion, a solution obtained by diluting 50g of trimer acid trimethyl ester with 70ml of diethyl ether was added dropwise for 120 minutes, and the reaction was performed while the temperature was kept below about 30°C. After the addition, stir for about 40 minutes, then carefully add 13 g of ion exchange water while cooling to deactivate the remaining reducing agent. The reaction solution is transferred to a flask containing 70 g of ice water, and 50 g of a 10% aqueous sulfuric acid solution is added. After standing, an appropriate amount of diethyl ether is added to the flask to extract the product. Repeated water washing until the ether layer becomes neutral, diethyl ether is distilled off, and 31 g of trimer triol containing three hydroxyl groups and a trivalent hydrocarbon group with a branched and cyclic structure and a carbon number of 54 is obtained. The obtained trimer triol is a viscous liquid at 25°C.
[0123] The following materials were used for the compounds (B) other than the compound B4. Compounds B8 and B9 are compounds other than compound (B). The carbon number, material name, and properties at 25° C. are recorded in parentheses. Compounds B1 to B3, B5 to B7, and 10 used reagents manufactured by Croda Japan Co., Ltd., and compounds B8, B9, and B11 used reagents from Sigma-Aldrich.
[0124] Compound B1: PRIPOL 1009 (hydrogenated dimer acid with 36 carbon atoms; containing two carboxyl groups and a divalent hydrocarbon group with a branched and cyclic structure; liquid)
[0125] Compound B2: PRIPOL 1040 (a trimer acid having 54 carbon atoms; containing three carboxyl groups and a trivalent hydrocarbon group having a branched and cyclic structure; liquid)
[0126] Compound B3: PRIPOL 2033 (dimer diol with 36 carbon atoms; contains two hydroxyl groups and a divalent hydrocarbon group with a branched and cyclic structure; liquid)
[0127] Compound B4: trimer triol obtained in Production Example 12 (carbon number 54; liquid)
[0128] Compound B5: Priamine 1071 (a mixture of a C36 dimer diamine (containing two amino groups and a divalent hydrocarbon group with a branched and cyclic structure, liquid) and a C54 trimer triamine (containing three amino groups and a trivalent hydrocarbon group with a branched and cyclic structure, liquid))
[0129] Compound B6: Priamine 1075 (a diamine dimer with 36 carbon atoms; containing two amino groups and a divalent hydrocarbon group with a branched and cyclic structure; liquid)
[0130] Compound B7: Docosanediolacid (straight-chain dibasic acid with 22 carbon atoms; solid)
[0131] Compound B10: PRIPOL 1004 (hydrogenated dimer acid having 44 carbon atoms; containing two carboxyl groups and a divalent hydrocarbon group having a branched and cyclic structure; liquid)
[0132] Compound B8: Oleic acid (monovalent straight-chain fatty acid with 18 carbon atoms; liquid)
[0133] Compound B9: Malonic acid (a divalent straight-chain fatty acid with 3 carbon atoms; solid)
[0134] Compound B11: 1,2,3-propanetricarboxylic acid (a trivalent straight-chain fatty acid having 6 carbon atoms; solid)
[0135] <Dispersion medium (C)>
[0136] The following materials were used as the dispersion medium (C). The acquired manufacturer's name, supplementary information and boiling point are shown in parentheses.
[0137] Dispersion medium C1: dihydroterpineol (manufactured by Japan Terpene Chemical Co., Ltd., boiling point 207°C)
[0138] Dispersion medium C2: isobornyl cyclohexanol (manufactured by Japan Terpene Chemical Co., Ltd., boiling point 318°C)
[0139] Dispersion medium C3: ISOPAR L (isoalkane with a boiling point of 199° C., manufactured by Andoh Parachemie Co., Ltd.)
[0140] Dispersion medium C4: Texanol (boiling point 244°C)
[0141] Dispersion medium C5: triethylene glycol monobutyl ether (glycol ether system, boiling point 278°C)
[0142] Dispersion medium C6: triethylene glycol monomethyl ether (glycol ether system, boiling point 248°C)
[0143] Dispersion medium C7: 2-ethyl-1,3-hexanediol (diol system, boiling point 244°C)
[0144] Dispersion medium C8: 1-decanol (boiling point 233°C)
[0145] Dispersion medium C9: diethylene glycol monomethyl ether (glycol ether system, boiling point 193°C)
[0146] Dispersion medium C10: 1-octanol (boiling point 194°C)
[0147] <Manufacturing of bonding paste>
[0148] [Example 1-1]
[0149] Metal particles A1 (92 parts), dihydroterpineol (8 parts) and compound B1 (1 part) were mixed using a rotation-revolution type mixer to prepare a bonding paste.
[0150] [Examples 1-2 to 1-32], [Comparative Examples 1-1 to 1-8]
[0151] According to the compositions described in Tables 1 and 2, except that the types and blending amounts of the materials were changed, a joining paste was obtained in the same manner as in Example 1-1.
[0152] [Examples 2-1 to 2-39], [Comparative Examples 2-1 to 2-6]
[0153] According to the compositions described in Tables 3 to 5, except that the types and blending amounts of the materials were changed, a joining paste was obtained in the same manner as in Example 1-1.
[0154] [Examples 3-1 to 3-45], [Comparative Examples 3-1 to 3-2]
[0155] According to the compositions described in Tables 6 to 8, except that the types and blending amounts of the materials were changed, a joining paste was obtained in the same manner as in Example 1-1.
[0156] <Evaluation of bonding paste (1)>
[0157] The bonding pastes obtained in Examples and Comparative Examples were used to prepare bonded bodies 1 by the method described below. The obtained bonded bodies 1 were evaluated as follows. The results are shown in Tables 1 to 8. In the tables, unless otherwise specified, the numerical values represent "parts", and blank columns represent that no compound was prepared.
[0158] [Preparation of joint body 1]
[0159] After printing the obtained joining paste once on the plated surface of the following joined part 1 under the following printing conditions, the plated surface of the following joined part 2 (chip) is placed toward the joining paste surface and heated under the following sintering conditions to obtain a joined body.
[0160] [Joined portion 1]
[0161] Gold-plated copper substrate: 20mm×20mm×3mm
[0162] [Joined portion 2]
[0163] Gold-plated SiC chip: 5mm×5mm×0.3mm
[0164] 〔Printing conditions (metal mask printing)〕
[0165] Metal mask: 4 mm square opening, 50 μm thickness (manufactured by SERIA CORPORATION)
[0166] Metal scraper: 40mm×250mm, thickness 1mm (manufactured by SERIA CORPORATION)
[0167] 〔Sintering conditions〕
[0168] The bonded body before sintering was placed in a hot air oven, and the temperature was raised from 25°C to 300°C at 2°C / min. After reaching 300°C, the temperature was maintained at 300°C for 2 hours.
[0169] [Metal mask printing suitability]
[0170] In the preparation of the bonded body 1 , the printability was evaluated according to the following criteria.
[0171] (Evaluation Criteria)
[0172] A: Printing is possible on the joined portion 1.
[0173] C: Printing cannot be performed on the joined portion 1 .
[0174] [Joint strength (initial, after hot and cold cycle test)]
[0175] The bonding strength (grain shear strength) of the obtained bonded body 1 was measured using the following measuring device and test conditions. In addition, "-" in Table 2 means that this evaluation was not carried out because printing could not be performed.
[0176] [Test conditions]
[0177] Measuring device: Universal bond strength tester (manufactured by Dage Japan Co., Ltd., 4000 series)
[0178] Measuring height: 100μm
[0179] Measuring speed: 500μm / s
[0180] Specifically, the joint body 1 is fixed at the position of the joined part 1, and the interface between the joined part 1 and the joining layer is pressed at a speed of 500 μm / s toward the joined part 2 at a height of 100 μm, and the joint strength at which the joint is destroyed is obtained. The joint strength (initial strength) just after the joint body 1 is made and the joint strength after the following cycle test are measured and evaluated based on the following evaluation criteria. The larger the numerical value of the strength, the better, and more than 15 MPa is within the practical range. The larger the numerical value of the evaluation criterion, the better, and the numerical value of the evaluation criterion of 2 or less indicates poor.
[0181] (Evaluation Criteria)
[0182] 5: 30MPa or more
[0183] 4: 20MPa or more and less than 30MPa
[0184] 3: 15MPa or more and less than 20MPa
[0185] 2: 5MPa or more and less than 15MPa
[0186] 1: Less than 5MPa
[0187] [Hot and cold cycle test]
[0188] The bonded body 1 was stored for 500 cycles, with one cycle consisting of keeping it at -40°C for 30 minutes, keeping it at 25°C for 15 minutes, and keeping it at 150°C for 30 minutes. Then, the bonded body was evaluated according to the same procedure and criteria as the above-mentioned bond strength evaluation.
[0189] <Reference: Evaluation of bonding paste (2)>
[0190] Using the bonding paste obtained in Examples 2-1 to 2-36, a bonded body 2-1 was prepared by the method described later. In addition, using the bonding paste obtained in Example 2-37 (equivalent to Example 2-20), a bonded body 2-2 was prepared by the method described later. The obtained bonded bodies 2-1 and 2-2 (hereinafter referred to as bonded bodies 2) were evaluated as follows. The results are shown in Tables 3 to 4. In the table, unless otherwise specified, the numerical value represents the portion, and a blank column indicates that it is not mixed.
[0191] [Preparation of Conjugate 2-1]
[0192] On one side of the following joined part 1, the joining paste obtained in Examples 2-1 to 2-36 is printed once under the following printing conditions, and then the plated surface of the following joined part 2 (chip) is placed toward the joining paste surface and heated under the following sintering conditions to obtain joint bodies.
[0193] [Joined portion 1]
[0194] Copper substrate (oxygen-free copper (C1020)): 20mm×20mm×1mm
[0195] [Joined portion 2]
[0196] Gold-plated SiC chip: 5mm×5mm×0.3mm
[0197] 〔Printing conditions (metal mask printing)〕
[0198] Metal mask: 4 mm square opening, 50 μm thickness (manufactured by SERIA CORPORATION)
[0199] Metal scraper: 40mm×250mm, thickness 1mm (manufactured by SERIA CORPORATION)
[0200] 〔Sintering conditions〕
[0201] The bonded body before sintering was placed in a calcining furnace, and the temperature was raised from 25°C to 300°C at 2°C / min in a nitrogen atmosphere. After reaching 300°C, the temperature was maintained at 300°C for 2 hours.
[0202] [Preparation of Conjugate 2-2]
[0203] Similar to the joint body 1, the joint paste obtained in Example 2-37 was printed once on one side of the joint part 1, and then placed in a hot air oven and dried at 170°C for 10 minutes. Then, the plated surface of the joint part 2 (chip) was placed toward the dried joint paste surface, and the joint part 2 was pressurized at a pressure of 20 MPa from above, and the temperature was raised from room temperature to 300°C at a condition of 20°C / min. After reaching 300°C, it was maintained at the temperature for 10 minutes to obtain a joint body.
[0204] [Joint strength (initial, after hot and cold cycle test)]
[0205] The bonding strength (grain shear strength) of the obtained bonded body 2 was measured using the following measuring device and test conditions.
[0206] [Test conditions]
[0207] Measuring device: Universal bond strength testing machine (manufactured by Dage Japan Co., Ltd., 4000 series)
[0208] Measuring height: 100μm
[0209] Measuring speed: 500μm / s
[0210] Specifically, the joint body 2 is fixed at the position of the joined part 1, and the interface between the joined part 1 and the joining layer is pressed at a speed of 500 μm / s toward the joined part 2 at a height of 100 μm, and the joint strength at which the joint is broken is obtained. The joint strength just after the joint body is made (initial joint strength) and the joint strength after the following cycle test (joint strength after 500 cycles) are measured and evaluated based on the following evaluation criteria. The larger the numerical value of the strength and the evaluation criteria, the better.
[0211] (Evaluation Criteria)
[0212] 5: 30MPa or more
[0213] 4: 20MPa or more and less than 30MPa
[0214] 3: 15MPa or more and less than 20MPa
[0215] 2: 5MPa or more and less than 15MPa
[0216] 1: Less than 5MPa
[0217] [Hot and cold cycle test]
[0218] The bonded body 2 was stored for 500 cycles, with one cycle consisting of keeping it at -40°C for 30 minutes, keeping it at 25°C for 15 minutes, and keeping it at 150°C for 30 minutes. Then, evaluation was performed according to the same procedure and criteria as the above-mentioned bonding strength evaluation method.
[0219] <Reference: Evaluation of bonding paste (3)>
[0220] Using the bonding paste obtained in Examples 3-1 to 3-40, a bonded body 3-1 was prepared by the method described below. In addition, using the bonding paste obtained in Example 3-41 (equivalent to Example 3-13), a bonded body 3-2 was prepared by the method described below. The obtained bonded bodies 3-1 and 3-2 (hereinafter referred to as bonded bodies 3) were evaluated as follows. The results are shown in Tables 6 to 7. In the table, unless otherwise specified, the numerical value represents the portion, and a blank column indicates that it is not mixed.
[0221] [Preparation of Conjugate 3-1]
[0222] On one side of the following joined part 1, each joining paste obtained in Examples 3-1 to 3-40 is printed once under the following printing conditions, and then the plated surface of the following joined part 2 (chip) is placed toward the joining paste surface and heated under the following sintering conditions to obtain a joint body.
[0223] [Joined portion 1]
[0224] Copper substrate (oxygen-free copper (C1020)): 20mm×20mm×2mm
[0225] [Joined portion 2]
[0226] Gold-plated SiC chip: 5mm×5mm×0.3mm
[0227] 〔Printing conditions (metal mask printing)〕
[0228] Metal mask: 4 mm square opening, 50 μm thickness (manufactured by SERIA CORPORATION)
[0229] Metal scraper: 40mm×250mm, thickness 1mm (manufactured by SERIA CORPORATION)
[0230] 〔Sintering conditions〕
[0231] The bonded body before sintering was placed in a calcining furnace, and the temperature was raised from 25°C to 300°C at 2°C / min in a nitrogen atmosphere. After reaching 300°C, the temperature was maintained at 300°C for 2 hours.
[0232] [Preparation of Conjugate 3-2]
[0233] Similar to the joint body 3-1, the joint paste obtained in Example 3-41 was printed once on one side of the joint part 1, and then placed in a hot air oven and dried at 170°C for 10 minutes. Then, the plated surface of the joint part 2 (chip) was placed toward the dried joint paste surface, and the joint part 2 was pressurized at a pressure of 20 MPa from above, and the temperature was raised from room temperature to 300°C at a rate of 20°C / min. After reaching 300°C, the temperature was maintained for 10 minutes to obtain a joint body.
[0234] [Joint strength (initial, after hot and cold cycle test)]
[0235] The bonding strength (grain shear strength) of the obtained bonded body 3 was measured using the following measuring device and test conditions.
[0236] [Test conditions]
[0237] Measuring device: Universal bond strength testing machine (manufactured by Dage Japan Co., Ltd., 4000 series)
[0238] Measuring height: 100μm
[0239] Measuring speed: 500μm / s
[0240] Specifically, the joint body 3 is fixed at the position of the joined part 1, and the interface between the joined part 1 and the joining layer is pressed at a speed of 500 μm / s toward the joined part 2 at a height of 100 μm, and the joint strength at which the joint is broken is obtained. The joint strength just after the joint body 3 is made (initial joint strength) and the joint strength after the following cycle test (joint strength after 500 cycles) are measured and evaluated based on the following evaluation criteria. The larger the numerical value of the strength and the evaluation criteria, the better.
[0241] (Evaluation Criteria)
[0242] 5: 30MPa or more
[0243] 4: 20MPa or more and less than 30MPa
[0244] 3: 15MPa or more and less than 20MPa
[0245] 2: 5MPa or more and less than 15MPa
[0246] 1: Less than 5MPa
[0247] [Hot and cold cycle test]
[0248] The bonded body 3 was stored for 500 cycles, with one cycle being 1 step of keeping at -40°C for 30 minutes, 25°C for 15 minutes, and 150°C for 30 minutes. Then, evaluation was performed according to the same procedure and criteria as the above-mentioned bond strength evaluation method.
[0249]
[0250]
[0251]
[0252]
[0253]
[0254]
[0255]
[0256] [Table 8]
[0257] Table 8.
[0258]
[0259] The results of Tables 1 to 8 show that when the bonding paste of the comparative example was used, the bonding strength was significantly low, and when the broken samples were observed after the grain shear test, the broken samples were found to be broken at the interface between the gold-plated SiC chip and the bonding layer.
[0260] On the other hand, when the bonding paste of the embodiment was used, the bonding strength was very high. It was confirmed that when the bonding paste of the embodiment was used, the printing adaptability was excellent and the bonding strength was very high even when the metal particles were contained at a high concentration, and the decrease in bonding strength was also suppressed after the hot and cold cycle test.
[0261] In particular, regarding the joining paste containing a dispersion medium (C) including a dispersion medium having a boiling point of 200° C. or higher, it was confirmed that even when a copper substrate that is difficult to undergo thermal cycling without plating treatment is used as a joined portion, the joining strength is very high, and a decrease in the joining strength is suppressed after a thermal cycling test.
[0262] In addition, regarding a bonding paste containing a compound having 3 carboxyl functional groups and 20 to 80 carbon atoms in an amount ranging from 0.05 to 2.7 parts by mass relative to 100 parts by mass of metal particles (A), it was confirmed that even when a copper substrate that was not plated and had a relatively thick thickness of 2 mm and was easily deteriorated by thermal cycling was used as the bonded portion, the bonding strength was very high, and the reduction in bonding strength was suppressed after the thermal cycling test.
Claims
1. A composition containing metal particles, comprising: metal particles (A) having an average particle size of 100 nm to 500 nm; and a compound (B) having two or more functional groups (b) and a carbon number of 20 to 80, wherein the functional group (b) is any one selected from a hydroxyl group, a carboxyl group and an amino group. 2 . The metal particle-containing composition according to claim 1 , wherein the number of the functional groups is 2 or 3. 3 . The metal particle-containing composition according to claim 1 , wherein the compound (B) has a branched and / or cyclic structure. 4 . The metal particle-containing composition according to claim 1 , wherein when the number of the functional groups is set to n, the compound (B) has an n-valent hydrocarbon group. 5 . The metal particle-containing composition according to claim 4 , wherein the n-valent hydrocarbon group has 30 to 60 carbon atoms. 6 . The metal particle-containing composition according to claim 1 , wherein the compound (B) comprises at least one selected from the group consisting of dimer acid, trimer acid, dimer diol, trimer triol, dimer diamine and trimer triamine. 7 . The metal particle-containing composition according to claim 1 , comprising 0.1 to 3 parts by mass of the compound (B) relative to 100 parts by mass of the metal particles (A). 8 . The metal particle-containing composition according to claim 1 , comprising 0.3 to 2.7 parts by mass of the compound (B) relative to 100 parts by mass of the metal particles (A). 9 . The metal particle-containing composition according to claim 1 , wherein the compound (B) contains a compound (Bx) having three carboxyl groups and having 20 to 80 carbon atoms. 10 . The metal particle-containing composition according to claim 9 , wherein the compound (Bx) is a trimer acid. 11 . The metal particle-containing composition according to claim 9 , wherein the compound (B) further contains a compound (By) having two carboxyl groups and having 20 to 80 carbon atoms. 12 . The metal particle-containing composition according to claim 11 , wherein the compound (By) is a dimer acid. 13 . The metal particle-containing composition according to claim 9 , comprising 0.05 to 2.7 parts by mass of the compound (Bx) based on 100 parts by mass of the metal particles (A). 14 . The metal particle-containing composition according to claim 1 , wherein the metal particles (A) have an average particle diameter of 150 nm to 450 nm. 15 . A joining paste comprising a dispersion medium (C) and the metal particle-containing composition according to claim 1 . 16 . The joining paste according to claim 15 , wherein the dispersion medium (C) contains a dispersion medium having a boiling point of 200° C. or higher. 17 . The joining paste according to claim 15 , wherein the dispersion medium (C) contains a dispersion medium having a boiling point of 250° C. or higher. 18 . The joining paste according to claim 15 , wherein the dispersion medium (C) comprises one or more selected from the group consisting of glycol ethers and glycols. 19 . The joining paste according to claim 15 , wherein the ratio of the mass of the metal particles (A) to the mass of the joining paste is 80% by mass to 95% by mass. 20 . A joined body formed by joining a first joined portion and a second joined portion using the joining paste according to claim 15 .
Citation Information
Patent Citations
Plastic lens material and its production
JP1998067835A
Joining material and joining method using the same
JP2011080147A
Bonding material and bonding method using the same
JP2011240406A
Joint material and joining method using same
JP2018109232A